Penerapan metode eksperimen pada mata pelajaran IPA materi sifat cahaya Sekolah Dasar - Okpatrioka, Okpatrioka; Nusantari, Ari (ARKA INSTITUTE, 2022)
Inappropriate teaching methods can cause student learning outcomes and interest in science subjects. Especially if the material is delivered in ways that are less interesting. One teaching method that is believed to improve learning outcomes is the experimental method. This study aims to describe the knowledge of teachers' understanding of the experimental method, the use of media, and the classroom atmosphere with the experimental method. The research method used is library research with a descriptive qualitative approach. Descriptive data was collected through written or spoken words from teachers and students observed. Relevant reading materials were selected from the library, such as books, dictionaries, journals, documents, and magazines. The criteria for selecting reading materials include novelty and relevance to the research. The results showed that the teacher was maximized in applying the experimental method on the properties of light, in accordance with the concept of knowledge about the experimental method. Thus, it can be concluded that the application of the experimental method has been optimal, allowing teachers to effectively describe the properties of light in learning at the elementary school level.